THE BASIC LEVEL OF TOTAL POWER OF HEART RATE VARIABILITY AND EFFICACY OF CHRONIC HEART FAILURE THERAPY - Yabluchansky, M.I.; Ignatkina, O.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The efficacy of the chronic heart failure (HF) therapy by enalapril maleat and metoprolol (MT) in clinical-haemodynamic indexes and parameters of the heart rate variability (HRV), depending of the initial values of total power (TP) of the HRV, at 98 patients were studied. The obtained results show that patients with HF need addition of MT as soon as possible, especially for the patients with lowest TP HRV level.